2012
DOI: 10.1590/s1415-43662012000300013
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização bioclimática de sistemas ao ar livre e confinado para a criação de matrizes suínas gestantes

Abstract: R ESU M OO confinamento de matrizes suínas foi criado com o intuito de maximizar a produtividade; entretanto, existem problemas relacionados ao bem-estar animal. Objetivou-se avaliar a criação de matrizes suínas gestantes no sistema de confinamento e ao ar livre, com relação ao ambiente térmico e às respostas fisiológicas. O experimento foi realizado em Monte Mor/SP. A avaliação fisiológica foi realizada por meio do registro das variáveis: frequência respiratória e temperatura de pele. Foram registradas as var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
1
5
0
1
Order By: Relevance
“…In this way, all the treatments, in all the evaluated schedules, presented enthalpy values below the recommended threshold value. The results found in this study agree with those observed by Nazareno et al (2012), who, although working with matrices (animals that use the same mechanisms of thermoregulation as pigs in the growth and finishing phase) in different breeding systems (confinement and not confinement), found enthalpy values of 49.84 and 47.87 kJ kg -1 , respectively.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In this way, all the treatments, in all the evaluated schedules, presented enthalpy values below the recommended threshold value. The results found in this study agree with those observed by Nazareno et al (2012), who, although working with matrices (animals that use the same mechanisms of thermoregulation as pigs in the growth and finishing phase) in different breeding systems (confinement and not confinement), found enthalpy values of 49.84 and 47.87 kJ kg -1 , respectively.…”
Section: Resultssupporting
confidence: 91%
“…The enthalpy values express the amount of energy contained in a mixture of dry air and water vapor, thus influencing the thermal changes between the animal and the environment (Nazareno et al 2012). According to Moura (1999), the desired enthalpy value for the pig growth phase is 60.44 to 68.62 kJ kg dry air -1 .…”
Section: Resultsmentioning
confidence: 99%
“…Piglets were more active during spring-time and cooler times of the days as compared to summer and warmer times of the day. During cooler temperatures piglets were more active and fed more intensively, whereas during warmer temperatures resting in the shade and wallowing were more frequent [48]. These authors concluded that environmental temperature and reduction in vegetative ground cover are important factors that impact behavior and productivity of pasture pigs [48].…”
Section: Exposure To Climatic Elementsmentioning
confidence: 99%
“…The enthalpy can be calculated in order to evaluate the thermal condition of the environment in which the animals are housed (H, ). According to Ferraz et al (2016), the H is interesting in the evaluation of thermal comfort, since it expresses the amount of energy contained in a mixture of dry air and water vapor, influencing the thermal changes between the animal and the environment (Nazareno et al, 2012). According to Rodrigues et al (2010), in case of changing relative humidity at the same dry-bulb temperature, there is a change in the energy involved in the process and hence the thermal changes are altered.…”
Section: Introductionmentioning
confidence: 99%